Biljana Plavšić at the ICTY: A Feminist Analysis of Representations of the Self - Kateřina Krulišová (Journal of Perpetrator Research, 2020)
This paper focuses on the legal defence of Biljana Plavšić before the United Nations International Criminal Tribunal for the Former Yugoslavia. It analyses the discursive strategies chosen by Plavšić in her plea of guilt. Utilising the theoretical concepts of motherhood, ‘Beautiful Soul’, double and triple transgressions, and Othering, together with legal and criminological debates on chivalry, Plavšić’s representations of herself and her actions during the war are critically analysed. Studying the case of Plavšić, this article aims to enrich the existing feminist debates on the representation of violent women in the media and in justice tribunals.